2022
DOI: 10.37762/jgmds.9-3.302
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Manual Vacuum Aspiration Vs Conventional Evacuation and Curettage

Abstract: OBJECTIVES: To evaluate the safety and efficacy of Manual Vacuum Aspiration (MVA) compared to Conventional Evacuation and Curettage (E & C) in managing first-trimester miscarriage. METHODOLOGY: A total of 160 patients were enrolled in this comparative study. Patients were categorized into two groups (Group A undergoing MVA) and (Group B undergoing E&C). Each group had 80 cases randomly selected. Stable patients with miscarriages ­< 12 wks of gestation and no comorbid were included in the study. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…It is important to follow established clinical guidelines and protocols for managing first-trimester miscarriage and to provide appropriate care, support, and counseling to patients during this challenging time 222,23,24 . They found complete abortion in 88% patients and 65% patients respectively in MVA group and misoprostol group.In study of Kishwar N et al, 17 higher (97.5%) efficacy rate was observed in MVA group.…”
Section: Discussionmentioning
confidence: 79%
“…It is important to follow established clinical guidelines and protocols for managing first-trimester miscarriage and to provide appropriate care, support, and counseling to patients during this challenging time 222,23,24 . They found complete abortion in 88% patients and 65% patients respectively in MVA group and misoprostol group.In study of Kishwar N et al, 17 higher (97.5%) efficacy rate was observed in MVA group.…”
Section: Discussionmentioning
confidence: 79%
“…Rehman F et al 13 compared control of PPH between Balloon Inflation and Uterovaginal Packing group. In balloon inflation methods control of PPH was found 55% patients, while in uterovaginal packing method had control of PPH in 85% patients.In a study conducted by Kishwar N et al 14 on 140 patients, The efficacy of both methods was observed to be 90% and 87.1%, respectively.…”
Section: Discussionmentioning
confidence: 96%